Tax Knowledge and E-Filling Socialization on Taxpayer Compliance - Herda Herda; Salim Assoba; Ewing Yuvisa Ibrani (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this research is to determine whether there is an influence between knowledge of taxation and tax socialization (e-filling system) towards taxpayer compliance at PT. Parkland World Indonesia is seen from the number of employees who do not report Notification (SPT) of more than 80% of the total number of employees of PT. As many as 5,632 Parkland World Indonesia employees still do not care about submitting SPT for the Article 21 Income Tax deduction. The method used in this study is a quantitative research method with survey research. The population used in this study were employees at PT. Parkland World Indonesia. Samples were taken by 98 employees using the Slovin formula. R-Square is 0.822, which means that 82.2% of the variation in taxpayer compliance can be explained by variations in both the independent variable knowledge of taxation and tax socialization (e-filling system). Based on the results, the knowledge variable taxation and Tax socialization (e-filling system) have a partial and significant effect on tax compliance.